Environmental migration and displacement: a new theoretical framework for the study of migration aspirations in response to environmental changes. Issue 4 (2nd October 2019) - Van Praag, Lore; Timmerman, Christiane
ABSTRACT: Migration has existed in all times and places and people have migrated for a variety of (combined) reasons: environmental, economic, political, humanitarian, social and cultural. While social and political conflicts that have arisen out of environmental changes are not new, environmental changes have placed some living conditions and other reasons for migration under even more pressure. In this paper, we combine insights from two approaches to the study of environmental migration and displacement – namely 'the sustainable livelihoods approach' and 'the new economics of labour migration' – and build further on existing models and theories of migration aspirations and dynamics. Based on these insights, we develop a theoretical framework on the study of migration aspirations and how they take shape within the existing structural constraints or capabilities for people living in areas heavily affected by environmental change using a multilevel perspective. The novelty of this model is that it focuses on migration aspirations when confronted with environmental changes. The multilevel approach, which includes the local social environment, incorporating the culture of migration of the living environment, one's personal local and transnational networks, perceptions on environmental changes and local discourses thereof, is therefore of particular relevance.